Pomen telesne dejavnosti v času širjenja koronavirusa - Zovko, Vinko (Šport (Ljubljana), 2020)
The coronavirus pandemic has changed our way of life. Many people were forced to stay and work from home. All group and individual workouts at sports indoor and also some outdoor centers were prohibited by law, so people who were otherwise physically active in organized exercise had to adapt to new circumstances. It was even more difficult for people who's every day didn't include any physical activity. Reducing physical activity has a negative impact on our health. On the contrary, regular physical activity has a positive effect on lowering high blood pressure, helping to manage weight and reducing the risk of heart disease, stroke, type 2 diabetes, various cancers. Physical activity also improves bone and muscle strength and improves balance, flexibility and fitness. In older people, balance exercises help prevent falls and injuries. It could be said, that physical activity during a pandemic acts as protective loop that reduces susceptibility to coronavirus infection.
Keywords: COVID-19; koronavirusi; physical activity; priporočila; recommendations; sport; šport; telesna aktivnost; telesna dejavnost